Jewish Mysticism as a Form of Feminism in Early 20th Century Hungarian Jewish Literature: Anna Lesznai’s Response to Otto Weininger - Rethelyi, Mari (Women in Judaism, 2022)
This article examines Anna Lesznai’s radical imagining of sex and its use for transcendental purposes that heavily rely on Jewish mystical ideas intertwined with Otto Weininger's theory of gender binarism. In her gender theory—part of feminist discourse at the turn of the twentieth century—Lesznai describes female love, using religious language and ideas from Jewish mysticism, especially those resembling Hassidic concepts, and ultimately compares sexual union to yihud- unio mystica with God. Working within the patriarchal understanding of the biological definition of gender and of the concept of "female difference," Lesznai’s feminism rooted in the belief that certain personality traits and skills are inherently gendered, but she reverses the hierarchy by placing women in the position of power, thus turning Jewish mysticism and Weininger’s gender philosophy on its head.